2022
DOI: 10.1002/hed.26996
|View full text |Cite
|
Sign up to set email alerts
|

Systematic construction and external validation of an immune‐related prognostic model for nasopharyngeal carcinoma

Abstract: Background We attempted to identify the most reliable immune‐related index for predicting nasopharyngeal carcinoma (NPC) prognosis and to reveal its precise and integrated relationship with NPC progression. Method One thousand seven hundred and six patients with newly diagnosed NPC (1320 from the primary cohort and 386 from the validated cohort) from January 2010 to March 2014 were enrolled. Clinical features and 12 immune‐related variables were analyzed. Results A high absolute lymphocyte count (ALC; >3.2 × 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…A high pretreatment lymphocyte count has been reported to be associated with a good prognosis of NPC, 25 and tumor-infiltrating lymphocytes are positive prognostic predictors in various cancers. 26 , 27 Our previous study 28 also confirmed absolute lymphocyte count as an important marker in predicting NPC survival. Platelets and CRP are also important factors affecting the inflammatory response, thereby affecting the prognosis of patients.…”
Section: Discussionsupporting
confidence: 52%
“…A high pretreatment lymphocyte count has been reported to be associated with a good prognosis of NPC, 25 and tumor-infiltrating lymphocytes are positive prognostic predictors in various cancers. 26 , 27 Our previous study 28 also confirmed absolute lymphocyte count as an important marker in predicting NPC survival. Platelets and CRP are also important factors affecting the inflammatory response, thereby affecting the prognosis of patients.…”
Section: Discussionsupporting
confidence: 52%
“…But, in the same guidelines there are the following statements "Due to the variability in assessments between laboratories, EBV DNA measurement needs further harmonization" … "However, more research is needed to refine the role of plasma EBV DNA in the management of NPC and to identify additional molecular markers which could lead to advances in personalised medicine in NPC" 8 . It is now a certain concept that systemic immunity and inflammation play a crucial role in the processes of tumour elimination, regression, and metastasis [80][81][82] . Lin et al performed a comparative analysis of 12 pre-treatment immune-related indices in a double-centre retrospective cohort of patients with NPC 82 .…”
Section: Surgerymentioning
confidence: 99%
“…It is now a certain concept that systemic immunity and inflammation play a crucial role in the processes of tumour elimination, regression, and metastasis [80][81][82] . Lin et al performed a comparative analysis of 12 pre-treatment immune-related indices in a double-centre retrospective cohort of patients with NPC 82 . The most significant were: absolute neutrophil count (ANC), absolute lymphocyte count (ALC), platelet count (PLT), levels of albumin (ALB), C-reactive protein (CRP), haemoglobin, and lactate dehydrogenase (LDH), neutrophilto-lymphocyte ratio (NLR), lymphocyte-to-monocyte ratio (MON), and platelet-to-lymphocyte ratio (PLR).…”
Section: Surgerymentioning
confidence: 99%